Achieving Medium Term Expenditure Framework Reform : A Case Study of Korea - Choi, Jae-Young; Park, Nowook (World Bank, Washington, DC, 2013)
A medium-term expenditure framework is considered an essential element of public financial management reform, and this framework has been adopted in many countries. However, in terms of implementation in those countries, the medium-term expenditure framework continues to present a significant challenge within the budget process. This case study provides an inside story of medium-term expenditure framework reform in the Republic of Korea and offers some suggestive evidence about the impact of the reform. Drawing on theories of change management, the study explores how actors within the Korean government created acceptance of reform needs among relevant stakeholders, how they handled various challenges throughout the reform, how they built capacity among stakeholders, and how they institutionalized the reform measures that were consistent with stakeholder incentives. The case highlights the following implications: (1) having strong support from top decision makers is essential to successful medium-term expenditure framework reform; (2) finding ways of integrating a medium-term expenditure framework into the budget process is critical; and (3) making the framework stable and sustainable requires both capacity building of relevant stakeholders and significant organizational restructuring.